A neurogenetics approach to defining differential susceptibility to institutional care. (March 2015) - Brett, Zoe H.; Sheridan, Margaret; Humphreys, Kate; Smyke, Anna; Gleason, Mary Margaret; Fox, Nathan; Zeanah, Charles; Nelson, Charles; Drury, Stacy
An individual's neurodevelopmental and cognitive sequelae to negative early experiences may, in part, be explained by genetic susceptibility. We examined whether extreme differences in the early caregiving environment, defined as exposure to severe psychosocial deprivation associated with institutional care compared to normative rearing, interacted with a biologically informed genoset comprising BDNF (rs6265), COMT (rs4680), and SIRT1 (rs3758391) to predict distinct outcomes of neurodevelopment at age 8 ( N = 193, 97 males and 96 females). Ethnicity was categorized as Romanian (71%), Roma (21%), unknown (7%), or other (1%). We identified a significant interaction between early caregiving environment (i.e., institutionalized versus never institutionalized children) and the a priori defined genoset for full-scale IQ, two spatial working memory tasks, and prefrontal cortex gray matter volume. Model validation was performed using a bootstrap resampling procedure. Although we hypothesized that the effect of this genoset would operate in a manner consistent with differential susceptibility, our results demonstrate a complex interaction where vantage susceptibility, diathesis stress, and differential susceptibility are implicated.